If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2g + -17 = 1 Reorder the terms: -17 + 2g = 1 Solving -17 + 2g = 1 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '17' to each side of the equation. -17 + 17 + 2g = 1 + 17 Combine like terms: -17 + 17 = 0 0 + 2g = 1 + 17 2g = 1 + 17 Combine like terms: 1 + 17 = 18 2g = 18 Divide each side by '2'. g = 9 Simplifying g = 9
| y-6=6(x+6) | | 7xc=-3 | | 8x-1+15x+3x+9=360 | | Z+5=5 | | 5x+7(-x-14)=-88 | | 13x-30=9 | | 10x+3+3x+24=180 | | 24x^2+-12x+-12=0 | | 22/25-7/10 | | 5/20=30/x | | 8x-1+15x+3x+9=90 | | y+4=4(x+7) | | -7y-7=-5(y+5) | | Log(4x+12)=2 | | 72x+56=-84-37x | | 3u-5=10 | | 5/20=3-/x | | 8x-1+15x+3x+9=180 | | 8x-6y=56 | | Q/6--112=125 | | 0=-16x^2+560 | | -9/p-3=3/5 | | 12=-7v+5(v+6) | | y+7=4(x-9) | | 20+-6n=-12+-2n | | 2w+30=460 | | cos(0.5)x=-1 | | 1/3x^2-10=18 | | -3x+2(4x-9)=-53 | | 7y-6=13y+6 | | 6x+3x=12y+11 | | 2r^2-8r-42=0 |